Dose–response association of 24-hour urine sodium and sodium to potassium ratio with nighttime blood pressure at older ages. (29th August 2020) - Kyung Kim, Mi; Kwon, Minji; Rhee, Moo-Yong; Kim, Kwang-Il; Nah, Deuk-Young; Kim, Sun-Woong; Gu, Namyi; Sung, Ki-Chul; Hong, Kyung-Soon; Cho, Eun-Joo; Jo, Sang-Ho
Abstract: Aims: We investigated the dose–response association of 24-hour urine sodium and potassium with 24-hour ambulatory blood pressure. Design: Cross-sectional community-based study. Methods: Among the 1128 participants in the community-based cross-sectional survey, 740 participants (aged 20–70 years) with complete 24-hour urine collection and valid 24-hour ambulatory blood pressure monitoring were included in the study. Participants were grouped into younger (<55 years, n  = 523) and older (≥55 years, n  = 217). Results: In the older population, nighttime blood pressure linearly increased with 24-hour urine sodium and the sodium to potassium ratio. For 24-hour urine sodium, adjusted β was 0.171 (95% confidence interval (CI) 0.036–0.305) for nighttime systolic blood pressure and 0.144 (95% CI 0.012–0.276) for nighttime diastolic blood pressure. For the 24-hour urine sodium to potassium ratio, adjusted β was 0.142 (95% CI 0.013–0.270) for nighttime systolic blood pressure and 0.144 (95% CI 0.018–0.270) for nighttime diastolic blood pressure. The 24-hour blood pressure linearly increased with the 24-hour urine sodium to potassium ratio and adjusted β was 0.133 (95% CI 0.003–0.262) for 24-hour systolic blood pressure and 0.123 (95% CI 0.003–0.244) for 24-hour diastolic blood pressure. Daytime blood pressure and 24-hour systolic blood pressure showed a significant but non-linear association with 24-hour urine sodium among the older population. In the younger population, 24-hour urine sodium, potassium and the sodium to potassium ratio were not associated with ambulatory blood pressure. Conclusion: In the older population, 24-hour urine sodium and the sodium to potassium ratio showed a linear and positive association with nighttime blood pressure, and 24-hour urine sodium was associated with 24-hour systolic blood pressure and daytime blood pressure in a non-linear fashion.